Systematic Variation in the Pattern of Gene Paralog Retention between the Teleost Superorders Ostariophysi and Acanthopterygii - la Serrana, Daniel Garcia de; Mareco, Edson A. [UNESP]; Johnston, Ian A. (Oxford University Press, 2014)
Teleost fish underwent whole-genome duplication around 450 Ma followed by diploidization and loss of 80-85% of the duplicated genes. To identify a deep signature of this teleost-specific whole-genome duplication (TSGD), we searched for duplicated genes that were systematically and uniquely retained in one or other of the superorders Ostariophysi and Acanthopterygii. TSGD paralogs comprised 17-21% of total gene content. Some 2.6% (510) of TSGD paralogs were present as pairs in the Ostariophysi genomes of Danio rerio (Cypriniformes) and Astyanax mexicanus (Characiformes) but not in species from four orders of Acanthopterygii (Gasterosteiformes, Gasterosteus aculeatus; Tetraodontiformes, Tetraodon nigroviridis; Perciformes, Oreochromis niloticus; and Beloniformes, Oryzias latipes) where a single copy was identified. Similarly, 1.3% (418) of total gene number represented cases where TSGD paralogs pairs were systematically retained in the Acanthopterygian but conserved as a single copy in Ostariophysi genomes. We confirmed the generality of these results by phylogenetic and synteny analysis of 40 randomly selected linage-specific paralogs (LSPs) from each superorder and completed with the transcriptomes of three additional Ostariophysi species (Ictalurus punctatus [Siluriformes], Sinocyclocheilus species [Cypriniformes], and Piaractus mesopotamicus [Characiformes]). No chromosome bias was detected in TSGD paralog retention. Gene ontology (GO) analysis revealed significant enrichment of GO terms relative to the human GO SLIM database for growth, Cell differentiation, and Embryo development in Ostariophysi and for Transport, Signal Transduction, and Vesicle mediated transport in Acanthopterygii. The observed patterns of paralog retention are consistent with different diploidization outcomes having contributed to the evolution/diversification of each superorder.
Keywords: fish evolution; ploidy; gene loss; whole-genome duplication